English Learning Management For Acceleration ProgramA Site Study At Sma Negeri 1 Purworejo - DEWI , LYNDA RATNA (2012)
The learning management of acceleration program should more superiority than the regular learning management. To serve the gifted and talented student, it needs the whole learning management service. In particular, this research aims to describe the English learning management for acceleration program at SMA Negeri 1 Purworejo. It consists of characteristic of English learning planning, characteristic of English learning processing and characteristic of English learning evaluating. Besides that, this research also aims to describe the superiority of English learning management for acceleration program. This research uses a qualitative approach. The data source informants of this research are English teacher of regular program, English teacher of acceleration program, chairman of acceleration program, vice principle of curriculum, and principle at SMA Negeri 1 Purworejo. The data collection techniques of this research are document study, observation and interview. The data analysis technique that is taken in this research, namely the data comparison of regular program and acceleration program, the combination of comparison result data with interview result, and the data interpretation. This research has shown that English learning planning for acceleration program at SMA Negeri 1Purworejo has characteristic of time allotment acceleration and enrichment of wide and deep indicator. The time allotment acceleration that is in syllabus and lesson plan of acceleration program seems clearly if two kinds of learning planning are compared with learning planning or regular program. The regular program planning of one semester has time allocation in six months, meanwhile acceleration program planning of one semester has time four months. The enrichment of learning planning for acceleration program appears in wide and deep indicator. The indicator of learning planning for acceleration program is diversified until language application level. The English learning processing of acceleration program has characteristic of trained student to stand-alone. The trained student of acceleration program seems clearly if it is compared the student activity of regular program in learning processing. In the elaboration, student of regular program still needs teacher guidance. The role of teacher in regular program is enough dominant. Meanwhile, in the elaboration activity, student of acceleration program had stood alone. The teacher of acceleration program has role-play as facilitator in learning. The English learning evaluating of acceleration program has characteristic of high claim. The evaluation claim of acceleration program is until using language namely listening, speaking, reading, and writing contextually.